Multiple In Vitro Analyses of Fracture Resistance in Maxillary Central Incisors Restored with Fiber Posts - Fariborz Vafaee; Masoumeh Khoshhal; Aliakbar Rezaei; Fereidon Sooltani; Mohsen Jalal zadeh; Ali Yalpaniyan; Farnaz Firooz; Ali Reza Izady; Ebrahim Yar Mohhamadi (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
INTRODUCTION: The resistance to fracture of endodontically treated teeth restored with esthetic post systems has not been extensively researched. This in vitro study compared the fracture patterns of endodontically treated teeth with esthetic post systems with different analysis methods. MATERIALS AND METHODS: A total of 26 recently extracted human maxillary central incisors were decoronated and then endodontically treated. Teeth were restored with quartz fiber posts. All posts were cemented with Panavia dual curing adhesive resin cement and subsequently restored with composite cores. Three methods were used to test fracture resistance. Each specimen was embedded in acrylic resin and then secured in a universal load-testing machine. A compressive load was applied at 135º degree angle at a crosshead speed of 1 mm/min to the long axis of the tooth until fracture occurred. The two other methods, finite element analysis (FEA) and photo elastic study used the same angulation and 90 N force to simulate the first method. The data were then compared. RESULTS: Clinical results indicated that fracture was most likely to occur between core and dentin, and then in the cervical 1/3 of the root. Photo elastic study demonstrated similar results; the highest stresses occurred at the junction of dentin and core contralateral to the side where force was applied. FEA also confirmed these results; however it also showed that the highest stresses arise at the dentin/core junction contralateral to the force point. CONCLUSION: All three techniques reiterate that the risk of fracture is greatest at the cervical dentin/core junction.